Learning Agroecology Online During COVID-19 - Félix, Georges F.; Sanfiorenzo, Andre (Frontiers in Sustainable Food Systems, 2022)
Since March 2020, the COVID-19 pandemic propelled the “stay-at-home” policy worldwide under public health uncertainty, resulting in increased individualization, as well as an increased reliance or dependency on digital communication technology. Based on revision of existing literature alongside a reflection on personal fieldwork experiences, we aim to: (1) describe major elements of agroecological pedagogy, (2) explore adaptation pathways to combine digitalization and participatory action-learning, and (3) briefly discuss opportunities challenges for agroecologists beyond COVID-19. Agroecological pedagogy is deeply embedded in the praxis, the scientific knowledge and ways of knowing (academic or not), and in the politics and agency of food movements. In line with Freire’s liberation pedagogy, seeing what already exists (e.g. in: ecosystems, home-gardens, fields, farms, watersheds) through participation and volunteering. Alongside a critical analysis to explain and explore certain phenomena, causes and consequences will likely result in the act leading to the implementation of transformative practices and novel designs that improve the state of any situation being addressed. Participatory action research/learning methods are strategic in agroecological pedagogy. Overall, the lockdown period led to increased societal digitalization of human interactions. During lockdown, however, the implementation of strategies for remote agroecology participatory action-learning were hampered, but not vanquished. Key changes to agroecology education projects “before” and “during” lockdown include an increased reliance on digital and remote strategies. Creative adaptations in the virtual classrooms were designed to nurture, deepen, and foster alternatives in favor of diverse knowledges and ways of knowing for food system transformations.